2022
DOI: 10.3390/ijerph19084774
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Job Resources in the Relationship between Job Demands and Work-Related Musculoskeletal Disorders among Hospital Nurses in Thua Thien Hue Province, Vietnam

Abstract: (1) Background: This cross-sectional study aimed to determine the moderating effect of job resources (JR) in the relationship between job demands (JD) and work-related musculoskeletal disorders (WRMSDs) among hospital nurses in the Thua Thien Hue province, Vietnam. (2) Methods: Data were collected via a self-reporting questionnaire administrated to 225 nurses from two hospitals in the Thua Thien Hue province of Vietnam from August to September 2020. The questionnaire included information on musculoskeletal sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Studies conducted by Mai, H.B. and Kim, J. on 265 Vietnamese participants revealed that most of the participants experienced work-related muscle skeletal disorders in their lower back (65.3%), neck and shoulder (61.8%), and knee (42.2%) [8]. Similar results were also identified in a study conducted on the Swedish population [9].…”
Section: Introductionsupporting
confidence: 73%
“…Studies conducted by Mai, H.B. and Kim, J. on 265 Vietnamese participants revealed that most of the participants experienced work-related muscle skeletal disorders in their lower back (65.3%), neck and shoulder (61.8%), and knee (42.2%) [8]. Similar results were also identified in a study conducted on the Swedish population [9].…”
Section: Introductionsupporting
confidence: 73%
“…However, few studies have investigated more severe MSDs in health professionals [ 5 ], which hinders our understanding of the factors that worsen MSD symptoms. However, certain data indicate that social support can reduce the damage of high physical demands on the severity of MSDs among health professionals [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain symptoms are also sources of stress, contributing to more severe symptoms [ 54 ]. Thus, the scale developed here can help identify the discomfort of health professionals as they are exposed to numerous physical occupational risks [ 7 ], including pulling, pushing, lifting instruments and equipment, and moving patients [ 55 ], but also to high psychological and psychosocial demands [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many scholars contend that job resource attributes such as supervisory support, job autonomy and performance feedback are correlated favorably with employee engagement levels (Chen and Fellenz, 2020;Kotz e and Nel, 2020;Mai and Kim, 2022). Subsequent reviews shed light on the relationship between selected job resources and employee engagement.…”
Section: Job Resources and Employee Engagementmentioning
confidence: 99%